Contribution of Vibrio parahaemolyticus Virulence Factors to Cytotoxicity, Enterotoxicity, and Lethality in Mice - Hiyoshi, Hirotaka (American Society for Microbiology (ASM), 2010)
Vibrio parahaemolyticus, one of the human-pathogenic vibrios, causes three major types of clinical illness: gastroenteritis, wound infections, and septicemia. Thermostable direct hemolysin (TDH) secreted by this bacterium has been considered a major virulence factor of gastroenteritis because it has biological activities, including cytotoxic and enterotoxic activities. Previous reports revealed that V. parahaemolyticus strain RIMD2210633, which contains tdh, has two sets of type III secretion system (T3SS) genes on chromosomes 1 and 2 (T3SS1 and T3SS2, respectively) and that T3SS1 is responsible for cytotoxicity and T3SS2 is involved in enterotoxicity, as well as in cytotoxic activity. However, the relative importance and contributions of TDH and the two T3SSs to V. parahaemolyticus pathogenicity are not well understood. In this study, we constructed mutant strains with nonfunctional T3SSs from the V. parahaemolyticus strain containing tdh, and then the pathogenicities of the wild-type and mutant strains were evaluated by assessing their cytotoxic activities against HeLa, Caco-2, and RAW 264 cells, their enterotoxic activities in rabbit ileal loops, and their lethality in a murine infection model. We demonstrated that T3SS1 was involved in cytotoxic activities against all cell lines used in this study, while T3SS2 and TDH had cytotoxic effects on a limited number of cell lines. T3SS2 was the major contributor to V. parahaemolyticus-induced enterotoxicity. Interestingly, we found that both T3SS1 and TDH played a significant role in lethal activity in a murine infection model. Our findings provide new indications that these virulence factors contribute to and orchestrate each distinct aspect of the pathogenicity of V. parahaemolyticus.